Mysteries of Asia - Spry-Leverton, Peter; Bell, Michael; Discovery Channel Video (Firm); Learning Channel (Firm); Café Productions Ltd (Bethesda, Md. Discovery Channel Video, 1999)
Documentary focusing on Angkor Wat, the extinct city in Cambodia. Examines the particular natural forces that encouraged the building of this vast Buddhist temple and how it relates to the history of Cambodia from ancient times through the rule of Pol Pot.
Produced for TLC by Café Productions, Ltd.
Narrator, Michael Bell.
Produced and directed by Peter Spry-Leverton ; edited by Jonathan Cooke.
Keywords: Anagkor Wat (Angkor); Temples, Buddhist -- Cambodia -- Angkor (Extinct city); Documentary films; Angkor (Extinct city) -- Buildings, structures, etc; Cambodia -- History